Eriodictyol inhibits the motility, angiogenesis and tumor growth of hepatocellular carcinoma via NLRP3 inflammasome inactivation - Wei Huang; Chenyang Wang; Hui Zhang (Heliyon, 2024)
NLRP3 involves in the development of hepatocellular carcinoma (HCC). Eriodictyol has shown its inhibitory effect on HCC cell proliferation. However, the underlying mechanism of eriodictyol in HCC is still unclear. This study aimed to explore the effect of and mechanism of eriodictyol on HCC. In this study, compared with eriodictyol (0 μM) group, eriodictyol significantly suppressed HepG2 cells (eriodictyol of 25, 50 and 100 μM) and Huh-7 cells (eriodictyol of 50 and 100 μM) viability, invasion, tube formation, metastasis-related genes MMP3, MMP16 and angiogenesis regulator VEGFA expressions with IC50 of 45.63 μM and 78.26 μM in vitro, respectively. Besides, eriodictyol significantly repressed NLRP3 expression, and reduced the protein levels of NLRP3 inflammasome-related proteins, adapter protein ASC, caspase-1, interleukin (IL)-18, and IL-1β in HepG2 (eriodictyol of 25, 50 and 100 μM) and Huh-7 cells (eriodictyol of 50 and 100 μM), respectively. Meanwhile, compared with control group, NLRP3 overexpression reversed the anti-metastatic effects of 100 μM eriodictyol on HCC cells invasion, tube formation, and metastasis-related genes MMP3, MMP16 and angiogenesis regulator VEGFA expressions, whereas NLRP3 knockdown enhanced the anti-metastatic effects of 100 μM eriodictyol on HCC cells. In vivo, compared with control group, eriodictyol significantly reduced the tumor growth, liver damage, inhibited the activation of NLRP3 inflammasome, and improved liver function, whereas NLRP3 overexpressing neutralized the anti-tumor effects of eriodictyol and degraded liver function. Hence, eriodictyol inhibited HCC cell viability, motility, angiogenesis and tumor growth via NLRP3 inflammasome inactivation both in vitro and in vivo.